The Influence of Work Climate, Leader Member Exchange (Lmx) and Organizational Commitment to Organizational Citizenship Behavior (Ocb) on Company Employees in Kudus City - Chornelia Fanny; Agus Sugiarto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Organizational Citizenship Behaviour is a reciprocal relationship between the organization and employees, employees who are satisfied with their work will show OCB. This study aims to determine the effect of work climate, leader member exchange, and organizational commitment to organizational citizenship behavior on company employees in Kudus City. The research method used is explanatory research with a quantitative approach where the variables are measured using a Likert scale, with a sample of 89 as many as 52 respondents. Data collection through questionnaire link. Data analysis techniques in this study using multiple linear regression analysis methods. The results showed that there was a positive influence between Work Climate, Leader Member Exchange, and Organizational Commitment to Organizational Citizenship Behavior on Employees.